A marine spatial data infrastructure in New Zealand: a systematic review on the cost-benefits. Issue 1 (2nd January 2019) - Griffin, Edward; Coote, Andy; Crompvoets, Joep
Abstract: In the context of the New Zealand case, this paper presents a review of international studies that use cost-benefit analysis to estimate the economic effects of marine spatial data infrastructures (MSDIs.).Cost-benefit ratios for investing in MSDIs range between 1:2 and 1:18. Benefits arise from efficiency of data collection, improved risk assessment for navigation, more effective marine spatial planning, supporting of marine science, reduced mineral exploration costs and disaster management. The research provides evidence for investing in an MSDI in New Zealand and stimulates debate on the varying methods underpinning economic studies in the marine geospatial context.